THE INFLUENCE OF THE DIGITAL-BASED TAX ADMINISTRATION SYSTEM ON TAXPAYER COMPLIANCE IN THE PANDEMIC - Kusumaningaji, Siam Pangestu; Zhafira, Adenia Deffa; Oktaviana, Ulfi Kartika (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
The largest and most influential source of revenue for the state is taxes. This article explains the effects of the digitalized tax administration system during the pandemic and the incentives provided by the government on taxpayer compliance. The study was conducted in the districts/cities located in Tulungagung, with a total of 55 observations obtained in this study. The data taken is after the year 2020, this due to the pandemic is bloomed in 2020. The data used in this research is quantitative data. This study uses primary data by questionnaires. Taxpayer Compliance is the dependent variable; Digital-based Tax Administration System is the independent variable. When viewed from the statistical test, partially the tax digitization system has a positive effect on taxpayer compliance carried out by individual taxpayers. Meanwhile, the statistical test simultaneously shows results that can be stated that the dependent variable has a significant effect on the independent variable. The tax administration digitization system has a positive effect on taxpayer compliance with individual taxpayers with incentives and changes in rates during the pandemic contained in the act. Tax harmonization, or (UU HPP).